Metalanguage : social and ideological perspectives - Cardiff Roundtable in Sociolinguistics 1998 : Newtown, Powys, Wales); Coupland, Nikolas, 1950-; Galasiński, Dariusz; Jaworski, Adam, 1957- (Berlin ; New York : Mouton de Gruyter, 2004)
"The ability of language to refer to itself, or its metalinguistic function, is explored in this volume through the study of explicit comments on speakers' own and other people's talk, reported speech, and stylisation. Metalanguage is theorized as an indispensable aspect of communication and as such an integral part of any sociolinguistic analysis. The book overviews the theory of metalanguage and presents original case studies of metalanguage in lay and professional (including linguists') discourses, the media, parliamentary debates, education, and retail shopping."--Jacket
Metalanguage : why now? / Adam Jaworski, Nikolas Coupland and Dariusz Galasinski -- pt. 1. Approaches to metalanguage -- Introduction to part 1 / Adam Jaworski and Nikolas Coupland -- Sociolinguistic perspectives on metalanguage : reflexivity, evaluation and ideology / Nikolas Coupland and Adam Jaworski -- Notes on the role of metapragmatic awareness in language use / Jef Verschueren -- Folk metalanguage / Dennis R. Preston -- pt. 2. Metalanguage and ideological construction -- Introduction to part 2 / Adam Jaworski and Nikolas Coupland -- Metalanguage in social life / Theo van Leeuwen -- Restoring the order : metalanguage in the press coverage of Princess Diana's Panorama interview / Dariusz Galasinski.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Ideology -- Congresses; Metalanguage -- Congresses; Sociolinguistics -- Congresses; Métalangage -- Congrès.; Sociolinguistique -- Congrès.; Idéologie -- Congrès.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Ideology; Metalanguage; Sociolinguistics; Metasprache; Soziolinguistik; Metataal; Newtown <Wales, 1998>; Conference papers and proceedings